Association of Ethnic Identity with Oral Health Knowledge, Attitudes, Behavior, and Outcomes on the Navajo Nation - Brega, Angela G. (J Health Care Poor Underserved, 2019)
American Indians and Alaska Natives (AI/ANs) experience poor oral health. Children and adults living on the Navajo Nation have a particularly high rate of dental decay. The literature suggests that health outcomes are often associated with the strength of one’s ethnic identity. We investigated the association of ethnic identity among Native parents with oral health knowledge, attitudes, behavior, and outcomes. Analyses used baseline data from a randomized controlled trial designed to reduce dental decay among AI/AN preschoolers enrolled in the Navajo Nation Head Start Program. Greater perceived importance of ethnic identity was associated with better oral health knowledge and attitudes but was unassociated with oral health behavior and was linked to worse oral health status. Parents who were better able to speak their tribal language had greater confidence in their ability to manage their children’s oral health, engaged in better oral health behavior, and reported better parental oral health status.